Non-uniform doping across the Fermi surface of NbS2 intercalates - Battaglia, Corsin; Cercellier, H.; Despont, L.; Monney, Claude; Prester, M.; Berger, H.; Forró, L.; Garnier, Michael Bernard Gunnar; Aebi, Philipp (My University, 2007)
Magnetic ordering of the first row transition metal intercalates of NbS2 due to coupling between the conduction electrons and the intercalated ions has been explained in terms of Fermi surface nesting. We use angle-resolved photoelectron spectroscopy to investigate the Fermi surface topology and the valence band structure of the quasi-two-dimensional layer compounds Mn1/3NbS2 and Ni1/3NbS2. Charge transfer from the intercalant species to the host layer leads to non-uniform, pocket selective doping of the Fermi surface. The implication of our results on the nesting properties are discussed.